Ecossistemas de aprendizagem e fluência digital nas aulas de língua inglesa - Silva, Luís Fernando da (2019)
The world experiences an immersion in the digital culture (Xavier, 2013) through the media genres. However, the public school environment finds it difficult to promote multiliteracies (Rojo, 2012) and, according to Ferretti (2012), ends up disregarding the demands of a technologically evolving society. Referring to language teaching, Cristovão (2012) warns that the classes mostly focus on reading, many of which are discouraging and disconnected from the students' reality. In order to contribute alternatives to face these challenges, the present work has its scope focused on the current educational configuration. In general, then, it was intended to create an educational product, called Gotcha!, to be used both inside and outside of school environment, in order to motivate and improve the teaching-learning process, especially, the English Language (EL) as Lingua Franca. This product materialized as an application for smartphones with Android or IOS operational system and it was designed to work both individually and as a team, seeking to promote teacher mediation with students. It sought to make sociological considerations (Mauss, 2003; Nogueira, 2005; Carvalho, 2007; Nogueira and Catani, 2007; Santos, 2008; Santos, 2011; Carneiro, 2012 and Brzézinski, 2018), in orde to support the contemporary Brazilian context to deal with these axes: education, technology and globalization. This study aimed to expose the philosophical-educational aspects that can contribute to a hybrid teaching proposal focusing on digital literacy; to propose a flipped classroom lesson plan with activities that might enable the development of the language capacities and the skills of production and oral and written comprehension; apply this prototype to high school EL students in a public school; discuss the positive and negative aspects of this educational product and its relation to the theoretical basis, in particular, to verify to what extent it contemplates the postulates of the Socio-discursive Interactionism (SDI) (Bronckart, 1999; Schneuwly and Dolz, 2004). For the accomplishment of this work, it was used an experimental and field research with qualitative character, so as to conjecture if mixed hybrid teaching with flipped classes and socio-interactionist approach based on genres can provide a motivating education that develops students as subject-subjects. The results show that to motivate students and improve the quality of teaching, teachers can use technological tools, customizing their classes so that learning is centered on students. It was also proved that the digital pedagogical tool chosen and the activities proposed therein showed compatibility, in practice, between the theory of learning ecosystems and the SDI.